Individual Approaches to Studying and the Affordances of Interacting with Networked Learning Environments - Smyth, Keith; Buckner, Kathy (Proceedings of the International Conference on Networked Learning, 2000)
This paper presents the general results of an investigation into networked learning via autonomously accessible, integrated environments which focused on individual approaches to studying, learning outcomes, and subjective descriptions of experience. Learners orientated towards understanding and possessing organised study methods performed most effectively, successfully acting upon the affordances of the environments. The implications are discussed.